DENTIFICATION OF DEVELOPING FACTORS TOURISM DESTINATION OF GEGAS LAKE IN SUKAKARYA SUBDISTRICT MUSI RAWAS DISTRICT SUMATERA SELATAN PROVINCE - Dian Mardiati Sari (Sekolah Tinggi Pariwisata Mataram, 2021)
The purposes of this study are: 1) To analyze the general description tourism destination of Gegas Lake; 2) To identify and analyze the determinants of the development tourism destination of of Gegas Lake. This research is descriptive. This sampling method consists of purposive sampling accidental sampling. Methods of data collection using interview techniques, observation, and questionnaires. The data were analyzed by using qualitative descriptive and quantitative descriptive. The results of the research are: 1) Lake Gegas tourism destination with an area of ± 6000 Hektar is located in Sugih Waras Village Sukakarya District which can be reached ± 48 km from Lubuk Linggau City and ± 30 km from the Capital Muarabeliti to Simpang Gegas. Tourist activities that can be done include relaxing and taking a walk on the outskirts of the lake, playing water near the dam waterfalls, traveling by boat and fishing. The facilities and services provided by the local community are public transport and motorcycle taxi services, providing food and beverage outlets and providing boat rentals. At Lake Gegas there are no facilities and services developed by entrepreneurs. While the facilities and services provided by the Regional Government of Musi Rawas Regency include improvements to the entrance to Lake Gegas, construction of gazebo, and stocking of fish seed; 2) The determinants of the development of Lake Gegas Tourism Destination, among others: the attractiveness of natural beauty and the attractiveness of tourism fisheries, the construction of more natural food and drinking establishments and religious facilities, the construction of water games and natural game facilities, the provision of electrical installations , repair of unpaved roads, provision of internet networks, and improvement of security systems and supervision and shelter development, enforcement of regulations and improvement of environmental management.